Strategi Pembelajaran Anak Tunarungu dalam Menghafal Al-Qur’an di Pesantren Tahfidz Difabel Baznas (BAZIS) Jakarta Selatan - Nabila, Mukfiyah Fuaydah; Rahmanto, Muhammad Arifin (ISLAMIKA, 2024)
The purpose of this study aims to see and also find out the learning strategy for deaf children in the method and process when memorizing the Qur'an as well as supporting factors and of course also the success inhibiting factors in learning to memorize the Qur'an for deaf students at the Jakarta Baznas (BAZIS) Difabel Tahfidz Pesantren. The research was conducted in the form of qualitative research. The population and place of this research were at the South Jakarta Baznas (BAZIS) Disabled Tahfidz Pesantren. Data collection was carried out by interview, observation and documentation. This data analysis involves three activities, namely data reduction, data presentation and drawing conclusions. The results found show that the learning strategy used in the cottage is a direct learning strategy. Where the teacher becomes the center of learning. The supporting factors in learning are: 1) the enthusiasm of santriwati, 2) learning methods, 3) adequate facilities. The inhibiting factors are: 1) changes in the mood of the santri, 2) the atmosphere of the class.